European Union: social or neoliberal? (Economic and Political Thought, 2015)
The birth of the European Union took place in the period of peak impactof neoliberal trends on the global economy. The mechanisms of the EU arefull of neoliberal ideas. This will prevent, over time, the implementation ofthe idea of social Europe formulated mainly by the European social democraticparties and nation states led by them. The mechanisms of neoliberalglobalisation will dominate the processes of European integration.